High‐Efficiency Dielectric Huygens' Surfaces. Issue 6 (1st February 2015) - Decker, Manuel; Staude, Isabelle; Falkner, Matthias; Dominguez, Jason; Neshev, Dragomir N.; Brener, Igal; Pertsch, Thomas; Kivshar, Yuri S.
<x xml:space="preserve">Abstract</x> Optical metasurfaces have developed as a breakthrough concept for advanced wave‐front engineering enabled by subwavelength resonant nanostructures. However, reflection and/or absorption losses as well as low polarization‐conversion efficiencies pose a fundamental obstacle for achieving high transmission efficiencies that are required for practical applications. Here, for the first time to our knowledge, highly efficient all‐dielectric metasurfaces are demonstrated for NIR frequencies using arrays of silicon nanodisks as metaatoms. The main features of Huygens' sources are employed, namely, spectrally overlapping crossed electric and magnetic dipole resonances of equal strength, to demonstrate Huygens' surfaces with full transmission‐phase coverage of 360° and near‐unity transmission. Full‐phase coverage combined with high efficiency in transmission are experimentally confirmed. Based on these key properties, all‐dielectric Huygens' metasurfaces can become a new paradigm for flat optical devices, including beam‐steering, beam‐shaping, and focusing, as well as holography and dispersion control.